Viral Transduction Enhancing Effect of EF‐C Peptide Nanofibrils Is Mediated by Cellular Protrusions. (23rd July 2021) - Schütz, Desiree; Rode, Sascha; Read, Clarissa; Müller, Janis A.; Glocker, Bernhard; Sparrer, Konstantin M. J.; Fackler, Oliver T.; Walther, Paul; Münch, Jan
Abstract: Self‐assembling peptide nanofibrils (PNF) have gained increasing attention as versatile molecules in material science and biomedicine. One important application of PNF is to enhance retroviral gene transfer, a technology that has been central for gene therapy approaches. The best‐investigated and commercially available PNF is derived from a 12‐mer peptide termed EF‐C. The mechanism of transduction enhancement depends on the polycationic surface of EF‐C PNF, which bind to the negatively charged membranes of viruses and cells, thereby overcoming electrostatic repulsions and increasing virion attachment and fusion. To better understand how EF‐C PNF interact with the cell surface, scanning electron and time‐lapse confocal microscopy were performed. The fibrils are found to be actively engaged by cellular protrusions such as filopodia. Consequently, chemical suppression of protrusion formation abrogates fibril binding and virion delivery to the cell surface of immortalized and primary T cells. Vice versa, induction of plasma membrane blebs result in increased fibril binding. Thus, the mechanism of PNF‐mediated viral transduction enhancement involves an active engagement of virus‐loaded fibrils by cellular protrusions, which may explain its superior performance over soluble transduction enhancers. Abstract : EF‐C peptide nanofibrils (PNF) efficiently promote retroviral viral gene transfer. Schütz et al. show that EF‐C PNF do not just randomly bind to the cell surface but are actively engaged by cellular protrusions, which frequently pull the fibrils towards the cell body. This may explain the superior performance of EF‐C PNF over other soluble transduction enhancers.